(3OQI GdZhGU hcfR GdGNJUGU aj eYQaI GdNhGUs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s ((3QLH ajGV GdScfOQi (B( (3GdcGJH GdYQHi HOjhGf eUQ (B) s)
(3ChdgG (B:s
(3hHYO (B: (3CjgG GdhGba Ydi SGMd HMQ CSQGQ GdNhGU hGdMce GdOGgT HHUQg Edi JdGWe CehGL JUGfja GdCee s
(3BNQgG (B:s
(3djchf JcedI ddahGFO hedLC dcd bGUO hefgdkG YPHkG dcd hGQO hGfJgi LejY GdcdGe hGfbVi hVY GdCbdGe s
(3fSNI eUhQI Yf GdeJMa GdHQjWGfi (B13965s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B43 s
Keywords: (3GdcjejGA h GdWHjYjGJs